Analysis of the Need for Social Studies Teaching Modules for Religious Moderation Based on Entrepreneurship and Disaster Mitigation - Astuti, Andarweni; Banowati, Eva; Prajanti, Sucihatiningsih Dian Wisika; ., Rusdarti (Journal of Ecohumanism, 2025)
This research aims to analyze the needs of junior high school Social Studies teachers in Semarang City regarding the development of independent curriculum teaching tools in the Social Studies learning process. A survey method was used in this research, with data analysis employing a qualitative descriptive approach. The primary informant was an Social Studies teacher at one of the religious junior high schools in Semarang City, and the supporting informants were junior high school students in Semarang City. The results of interviews and observations indicate that Social Studies learning still revolves around students, the teaching methods used are still conventional, and Social Studies teachers do not yet have Social Studies teaching modules that are suitable for the independent curriculum. The independent curriculum in primary and secondary education emphasizes character formation, including religion-based entrepreneurial moderation and disaster mitigation. This research provides a better understanding of the needs of Social Studies teachers in developing Social Studies teaching tools that are suitable for the independent curriculum. The results of this study are expected to serve as the basis for the development of more effective teaching strategies in achieving the goals of the independent curriculum, especially in terms of religion-based entrepreneurial moderation and disaster mitigation in Social Studies learning in junior high schools in Semarang City.